Graphic Novels and Climate Change: A Comparative Approach to the Teaching of Literature - Lima, João Vítor de; Silva, Suênio Stevenson Tomaz da (Revista Letras Raras, 2024)
Ecocriticism, as a means of analyzing literary texts, has been gaining increasing prominence in academic discussions. One of the reasons lies in its interdisciplinary nature inherent in the commonly mobilized definition: the study of the relationship between literature and the environment (Glotfelty, 1996). This idea, therefore, finds support in the field of comparative studies. Given the above, we propose this paper, with its main objective being to compare two graphic novels, namely Climate Changed: A Personal Journey Through the Science by Philippe Squarzoni, and HERE by Richard McGuire. Both published in 2014, these books interact with each other in various aspects, especially regarding the literary genre to which they belong: cli-fi [climate change fiction]. Thus, the theme of climate emergency is the guiding concept of this comparative analysis, in which we highlight the recurring motifs in both novels. Additionally, we expand, in a broader sense, the debate about the potential of this type of fiction in the context of teaching literature, paying attention to the most urgent issue of the moment: global climate imbalance. When writing this article, we anchored our reflections on the discussions of several scholars, including: Garrard (2006), Mehnert (2016), Siperstein, Hall, and LeMenager (2017), Durão and Cechinel (2022), and Remak (2011).